The new geography of subsea cables. (Economist, 2026)
The article focuses on how geopolitical tensions and the AI-driven demand for data are reshaping global undersea cable routes, bringing renewed strategic importance to remote islands in the Indian Ocean. Topics include the historical significance of the Cocos Islands, the development of new fibre-optic cable networks, and efforts to improve the security and resilience of global communications infrastructure.